2007
DOI: 10.1007/s00167-007-0437-2
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic screw fixation of large anterior glenoid fractures

Abstract: Ten patients after traumatic shoulder dislocation with resulting instability due to an acute anterior glenoid fracture involving at least 21 percent of the glenoid length were treated by arthroscopic screw fixation of the fragment. The average fragment size measured 26.2% of the glenoid length. Pre- and postoperative radiographic evaluations were performed with three-dimensional CT scans. A cannulated titanium screw system was used for fragment fixation. All ten patients were followed up radiographically and, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
13

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 26 publications
2
58
0
13
Order By: Relevance
“…Tauber et al [26] reported 10 patients with a large glenoid fracture treated by arthroscopically assisted percutaneous screw fixation. With a minimum follow-up of 24 months, the study showed good or excellent midterm clinical results for 90% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Tauber et al [26] reported 10 patients with a large glenoid fracture treated by arthroscopically assisted percutaneous screw fixation. With a minimum follow-up of 24 months, the study showed good or excellent midterm clinical results for 90% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Akute kleinere Pfannenrandläsionen werden in der Literatur kontrovers behandelt. Verschiedene Autoren zeigen sehr gute und gute Resultate nach arthroskopischer Refixation im Kurzzeit-Follow-up [20][21][22][23]. Demgegenüber zeigen jedoch andere Autoren Resorptionen der Fragmente von bis zu 70% [24], was mit der Erfahrung der Autoren einhergeht und höhere Reluxationen zeigt.…”
Section: Behandlung Und Prognoseunclassified
“…La riduzione e sintesi chirurgica di alcuni tipi di fratture glenoidee sta vivendo una fase di transizione dalle tecniche a cielo aperto a quelle artroscopiche, come evidenziato in questo stesso fascicolo (si veda "Il trattamento artroscopico delle fratture glenoidee" di M. Saporito et al a pag. 25) e le tecniche artroscopiche sono oggi una importante opzione di trattamento per le fratture glenoidee che possono essere ridotte artroscopicamente e stabilizzate con l'utilizzo di viti cannulate [1].…”
Section: Epidemiologiaunclassified
“…Le indicazioni all'intervento rimangono quindi quelle classiche sopra riportate, adattate ai singoli pazienti e alle concrete possibilità di una osteosintesi valida. Criteri primari sono l'instabilità della spalla e soprattutto i frammenti anteriori o posteriori di grosse dimensioni decalati medialmente in soggetti giovani, che si ritiene debbano essere trattati in funzione preventiva per una instabilità recidivante [1]. Oggi la riduzione e sintesi di una frattura di glena di Tipo I può essere eseguita a cielo aperto con una via d'accesso anteriore o posteriore (20 pazienti nella nostra esperienza) oppure, sempre più frequentemente, con una tecnica artroscopica (6 pazienti) (Fig.…”
Section: Diagnosi E Classificazioneunclassified